2017
DOI: 10.1208/s12248-017-0094-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Sensitive Measurement of IL-17A and IL-17F in Psoriasis Patient Serum and Skin

Abstract: Interleukin 17 is a family of cytokines that play a central role in many autoimmune and inflammatory diseases. IL-17A has been implicated as a key driver of psoriasis, mediating a chronic cycle of T-cell activation, keratinocyte proliferation and angiogenesis. It has been hypothesized that expression of IL-17A and the related cytokine IL-17F could be used as predictive biomarkers for therapeutic response, though they have been difficult to measure locally or in circulation because of their low abundance. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 13 publications
2
31
0
Order By: Relevance
“…In this study, we used a highly sensitive measurement for serum IL‐17 in a large cohort of patients with psoriasis treated with tofacitinib or etanercept. In PASI75 responders to tofacitinib and etanercept, serum IL‐17A concentrations at weeks 4 and 12 decreased to a much larger extent than in nonresponders, and reached low levels that were within the range previously reported in normal subjects (0.057–0.269 pg/mL) . Although tofacitinib and etanercept do not block IL‐17 signalling directly, the association between decreases in IL‐17A and clinical response suggests that normalization of circulating IL‐17A is required for psoriasis remission regardless of the therapeutic agent.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In this study, we used a highly sensitive measurement for serum IL‐17 in a large cohort of patients with psoriasis treated with tofacitinib or etanercept. In PASI75 responders to tofacitinib and etanercept, serum IL‐17A concentrations at weeks 4 and 12 decreased to a much larger extent than in nonresponders, and reached low levels that were within the range previously reported in normal subjects (0.057–0.269 pg/mL) . Although tofacitinib and etanercept do not block IL‐17 signalling directly, the association between decreases in IL‐17A and clinical response suggests that normalization of circulating IL‐17A is required for psoriasis remission regardless of the therapeutic agent.…”
Section: Discussionmentioning
confidence: 78%
“…Serum concentrations of IL‐17A/A homodimer (IL‐17A) and IL‐17A/F heterodimer (IL‐17A/F) were measured by validated methods, using commercial kits (Singulex Inc., Alameda, CA, USA) and immunoassays were performed (Erenna ® Immunoassay System; Singulex Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…To understand the mechanisms for the induction of MMPs in skin, IL-17-related inflammatory models are important. Indeed, the significance of IL-17 was reported in autoimmune diseases such as psoriasis [15], bullous pemphigoid (BP) [16,17], and alopecia areata [18]. Among them, Riani et al [16] reported that IL-17 increased CXCL10 in inflammatory cells, leading to an augmented secretion of MMP9 from neutrophils and monocytes in BP patients.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, we expect that IL-17A exerted its effect at local inflammatory sites of psoriatic skin rather than the circulation. Another possibility is that Mo-MDSCs downregulate IL-17A levels in circulation [31]. e transcription factor ROR-c plays a critical role in the expression of proinflammatory cytokine IL-17 in patients with psoriasis [32] and is, therefore, an attractive target for the treatment of psoriasis [33].…”
Section: Discussionmentioning
confidence: 99%